2018
DOI: 10.1089/mdr.2017.0150
|View full text |Cite
|
Sign up to set email alerts
|

Extended-Spectrum Beta-Lactamase-/AmpC Beta-Lactamase-Producing Enterobacteriaceae in Broiler Farms: Transmission Dynamics at Farm Level

Abstract: The occurrence of extended-spectrum beta-lactamase- (ESBL) and/or AmpC beta-lactamase- (AmpC) producing Enterobacteriaceae in livestock, especially in broiler fattening flocks, has been demonstrated in previous studies. Nevertheless, data on transmission routes of these resistant bacteria into the fattening farms are rare. Therefore, seven broiler fattening flocks were investigated for the occurrence of ESBL-/AmpC-producing Enterobacteriaceae during the course of the fattening period with the special focus on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(92 citation statements)
references
References 34 publications
3
88
1
Order By: Relevance
“…Isolates of fattening flocks C/41, F/74 and E/74 occurred with different prevalence in the respective fattening flocks (flock C/41: 73.1%, flock E/74: 26.4%, flock F/74: 5.7%). The second strain set included 42 isolates from investigations of seven different broiler production chains covering all detected genetic profiles (phylogroup + ESBL‐/pAmpC gene) to get an overall impression on cellulose and curli production in different resistant isolates from the whole broiler production chain (Daehre et al ., 2017; Projahn et al ., 2017) (Tables S1 and S2). Isolates of the first set showed both, production of cellulose and curli, regardless of the flock prevalence, whereas in the second one, various phenotypes were determined (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Isolates of fattening flocks C/41, F/74 and E/74 occurred with different prevalence in the respective fattening flocks (flock C/41: 73.1%, flock E/74: 26.4%, flock F/74: 5.7%). The second strain set included 42 isolates from investigations of seven different broiler production chains covering all detected genetic profiles (phylogroup + ESBL‐/pAmpC gene) to get an overall impression on cellulose and curli production in different resistant isolates from the whole broiler production chain (Daehre et al ., 2017; Projahn et al ., 2017) (Tables S1 and S2). Isolates of the first set showed both, production of cellulose and curli, regardless of the flock prevalence, whereas in the second one, various phenotypes were determined (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the small number of SNP differences between the isolates, a transmission or exchange of these ESBL E. coli between the barns of the same farm is very likely. It was previously shown that (ESBL‐) E. coli can survive the cleaning and disinfection procedures in the chicken barns which finally leads to a spread and the colonization of broiler chickens on the same farms (Luyckx et al ., 2015a,b; Daehre et al ., 2017). Interestingly, the two clusters differ in up to 629.4 SNPs Mbp −1 indicating that two different clonal lines of ST‐117 strains were introduced into the same flock.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations